Autonomic cardio‐respiratory reflex reactions and superselective ophthalmic arterial chemotherapy for retinoblastoma. Issue 10 (13th May 2013) - Phillips, Trudie J.; McGuirk, Simon P.; Chahal, Hardeep K.; Kingston, Judith; Robertson, Fergus; Brew, Stefan; Roebuck, Derek; Hungerford, John L.; Herod, Jane
Summary: Objective: To describe our experience with superselective ophthalmic artery chemotherapy (SOAC) in retinoblastoma and to report the serious adverse cardio‐respiratory reactions we have observed. Methods: SOAC was performed using a standardized protocol for general anesthesia, ophthalmic artery catheterization, and pulsed infusion of melphalan. Adverse reactions were defined as those in which the patient required active treatment to maintain cardio‐respiratory stability. Results: Between December 2008 and May 2012, 54 eyes in 52 patients were treated. 143 catheterization procedures were performed, with a technical success rate of 93% ( n = 133). There were no deaths or major complications. Adverse cardio‐respiratory reactions developed during 35 procedures (24%; 95% CI, 18–32%). All reactions occurred during second or subsequent catheterization procedures (39%; 95% CI, .29–49%) and were characterized by hypoxia, reduced lung compliance, systemic hypotension and bradycardia. Adverse events were successfully treated in all patients. One procedure was abandoned due to prolonged hemodynamic instability. Conclusion: Adverse cardio‐respiratory reactions are commonly observed in SOAC for retinoblastoma. We believe that the adverse clinical signs represent an autonomic reflex response, akin to the trigemino‐cardiac or oculo‐respiratory reflexes, and all patients should be considered at‐risk. Reactions occur only during second or subsequent procedures and can be life‐threatening. The routine use of intravenous atropine does not seem to have altered the incidence or severity of these reactions. Anesthetists and interventional neuroradiologists involved in SOAC must be vigilant to ensure adverse reactions, when they develop, are treated quickly and effectively.